2000
DOI: 10.1046/j.1365-2958.2000.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the in vivo acceptors of the mycoloyl residues transferred by the corynebacterial PS1 and the related mycobacterial antigens 85

Abstract: SummaryMycolic acids, long-chain (C 70 ±C 90 ) a-alkyl, bhydroxy fatty acids, are characteristic cell envelope components of mycobacteria; similar but shorterchain substances occur in corynebacteria and related taxa. These compounds apparently play an important role in the physiology of these bacteria. The deduced N-terminal region of PS1, one of the two major secreted proteins of Corynebacterium glutamicum encoded by the csp1 gene, is similar to the antigens 85 complex of Mycobacterium tuberculosis which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 52 publications
8
130
0
Order By: Relevance
“…Unusually for Gram-positive bacteria, their cell walls contain a characteristic hydrophobic layer (Minnikin & O'Donnell, 1984;Nikaido et al, 1993). It was shown that this layer plays an important role in drug and substrate permeability (Jarlier & Nikaido, 1990;Puech et al, 2000). In contrast to the Gram-negative bacteria, where the outer membrane is composed of phospholipids and lipopolysaccharides, the predominant constituents of the outer lipid layer of corynebacteria and related taxa are the mycolic acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…Unusually for Gram-positive bacteria, their cell walls contain a characteristic hydrophobic layer (Minnikin & O'Donnell, 1984;Nikaido et al, 1993). It was shown that this layer plays an important role in drug and substrate permeability (Jarlier & Nikaido, 1990;Puech et al, 2000). In contrast to the Gram-negative bacteria, where the outer membrane is composed of phospholipids and lipopolysaccharides, the predominant constituents of the outer lipid layer of corynebacteria and related taxa are the mycolic acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…15) These homologous proteins mediate the transfer of the mycolate residue to trehalose monomycolate. [16][17][18] A C. glutamicum homolog of mycobacterial polyprenyl monophosphomannose synthetase, which is involved in mycolate-layer formation, was also identified. 19) Recently, an emb gene encoding a possible target enzyme of EMB was cloned from C. glutamicum.…”
mentioning
confidence: 99%
“…It has been reported that a cspA mutant derived from the C. glutamicum CGL2005 strain contains 50% less cell wall-bound corynomycolates. 12) A cspA mutation also caused a similar reduction of cell wall-bound corynomycolates in the C. glutamicum ATCC13032 strain. 16) Corynebacteria and mycobacteria are phylogenetically related and share a similar cell-wall structure that contains (coryno)mycolic acids.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that mutations of cspA resulted in decreases in the amount of corynomycolate covalently bound to arabinogalactan, and non-covalently bound trehalose dicorynomycolate. 12,16) It is known that the mycolate layer functions as a permeability barrier against antibacterial agents and against host defense systems. [7][8][9] To identify defects in the mycolate layer of the ÁcspA mutant strains, the antibacterial susceptibility of wildtype strain ATCC13869 and the ÁcspA and ÁcspB mutant strains were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation